2009
DOI: 10.1093/sleep/32.2.150
|View full text |Cite
|
Sign up to set email alerts
|

The New AASM Criteria for Scoring Hypopneas: Impact on the Apnea Hypopnea Index

Abstract: This study demonstrates that using different published standard hypopnea definitions leads to marked differences in AHI. These results provide insight to clinicians and researchers in interpreting results obtained using different published standard hypopnea definitions, and they suggest that consideration should be given to revising the current scoring recommendations to include a single standardized hypopnea definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
442
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(463 citation statements)
references
References 23 publications
10
442
0
11
Order By: Relevance
“…However, even within the relative objectivity of these criteria, there are still variations among researchers in diagnostic thresholds for airflow reduction, oxygen de-saturation and cortical arousal (15).…”
Section: A Continuum Of Snoring?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even within the relative objectivity of these criteria, there are still variations among researchers in diagnostic thresholds for airflow reduction, oxygen de-saturation and cortical arousal (15).…”
Section: A Continuum Of Snoring?mentioning
confidence: 99%
“…However, apart from the rarely applied "gold standard" PSGs, none is a reliable marker of snoring status. 15 …”
Section: Distinguishing and Evaluating Types Of Snoringmentioning
confidence: 99%
“…The results showed that AHI (as a continuous variable) was significantly associated with hs-CRP (model 2, β=0.125, p=0.009) and also had a significant association with hs-CRP (model 2, β = 0.533, p=0.005) for severe OSA (as a categorical variable) when compared to the non-OSA group after being adjusting for age, smoking, drinking, and MetS status [1]. Based on the American Academy of Sleep Medicine (AASM) consensus report, the severity of OSA by classification of AHI is commonly used, such as severe OSA (AHI >30/h), moderate OSA (AHI, 15-30/h), persons at risk for OSA (AHI, 5-14/h), and normal persons (AHI <5/h) [2]. Therefore, we believe that OSA classification can provide more detailed and useful information to readers.…”
Section: Dear Editormentioning
confidence: 99%
“…Inclusion of hypopneas in the indices of disease spectrum is intended to reflect ventilatory insufficiency by defining periods of reduced respiration. Developing more accurate measurements of inspired and expired airflow, and then providing more precise definitions for hypopneas, will be paramount for determining how mild, moderate and severe ventilation insufficiency are associated with clinically identifiable consequences such as magnitude of oxygen desaturation or duration of arousal from sleep.The recent study by Dr. BaHamman and colleagues, examines the impact of altering the hypopnea definition on the indices of sleep breathing [4] as described for previous updates to scoring consensus [5]. In the current manuscript, the authors examine how changing the requisite percentage for reduction in airflow, and threshold level for oxygen desaturation and association with arousal, alters the distribution and significance of the clinical thresholds for disease.…”
mentioning
confidence: 99%
“…The recent study by Dr. BaHamman and colleagues, examines the impact of altering the hypopnea definition on the indices of sleep breathing [4] as described for previous updates to scoring consensus [5]. In the current manuscript, the authors examine how changing the requisite percentage for reduction in airflow, and threshold level for oxygen desaturation and association with arousal, alters the distribution and significance of the clinical thresholds for disease.…”
mentioning
confidence: 99%